2019
DOI: 10.2147/dddt.s203094
|View full text |Cite
|
Sign up to set email alerts
|

<p>Icariin Alleviates IL-1β-Induced Matrix Degradation By Activating The Nrf2/ARE Pathway In Human Chondrocytes</p>

Abstract: ObjectiveOsteoarthritis (OA) is characterized by progressive matrix destruction of articular cartilage. This study aimed to investigate the potential antioxidative and chondroprotective effects and underlying mechanism of Icariin (ICA) in interleukin-1 beta (IL-1β)-induced extracellular matrix (ECM) degradation of OA cartilage.MethodsHuman chondrocyte cell line HC-A was treated with different doses of ICA, and then MTT assay and PI staining were used to estimate ICA-induced chondrocyte apoptosis. Intracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…Paeoniflorin suppresses osteoclast differentiation by controlling the receptor activator of nuclear factor-κ B ligand (RANKL)/osteoprotegerin (OPG) ratio [ 12 ]. Furthermore, icariin and paeoniflorin were also proven to regulate the activity of chondrocytes and inhibit articular cartilage degradation [ 13 , 14 ]. These studies hinted that WB was a promising candidate drug for joint protection in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin suppresses osteoclast differentiation by controlling the receptor activator of nuclear factor-κ B ligand (RANKL)/osteoprotegerin (OPG) ratio [ 12 ]. Furthermore, icariin and paeoniflorin were also proven to regulate the activity of chondrocytes and inhibit articular cartilage degradation [ 13 , 14 ]. These studies hinted that WB was a promising candidate drug for joint protection in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…The role of IL‐1 as a key mediator of cartilage destruction especially in osteoarthritis was described by the early 1990s 9,10,44 . Recent studies have focused on IL‐1 and the IL‐1 receptor as targets for inhibiting and preventing IL‐1 related damage to cartilage and tissues 45–47 . Future study is warranted into whether similar approaches using targeted immunomodulation may be taken to improve fracture healing in infected conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Icariin has been shown to increase chondrocyte viability by promoting hypoxia-inducible factor-1α expression and anaerobic glycolysis 16,17 and inhibits chondrocyte apoptosis and angiogenesis by regulating the TDP-43 signaling pathway 18 . Zuo et al demonstrated that icariin alleviated IL-1β-induced matrix degradation and eliminated reactive oxygen species by activating the Nrf2/ARE pathway in human chondrocytes in vitro 19 .…”
Section: Discussionmentioning
confidence: 99%